Augustine and Confucian Virtues: Mencius and Augustine on the Proper Motivations for Moral Conduct - He, Teng (Religions, 2023)
In this essay, we analyze Mencius’s ethics through the lenses of Augustine’s critique of pagan virtue and its tendency to self-love. In the first part of this essay, we outline the basic conceptual framework of Augustine’s theory of virtue and the brunt of his criticism of the pagan virtue tradition. In the latter part, we explore how Mencius manages to avoid the Augustinian charge against the pagans that they render virtue subservient to honor, and how he largely agrees with Augustine on what place public performance of virtuous deeds should have. At the same time, Mencius’s emphasis on loving virtue for its own sake at times slides into expressions of taking delight in one’s own virtue, a subtler form of self-love that Augustine identifies especially in the Stoic philosophy. While Mencius gives space to the role of Heaven in his ethic, he lacks the theocentric pathos of Augustine, which includes, inter alia, an acknowledgment of our human frailty and deep dependence on God’s grace. Although Mencius’s ethical ideas ultimately correspond rather to those that Augustine associates with pagan virtue, Mencius represents at least a “higher” form that finds meaningful common ground with Augustine on several important issues.